Analisis Manajemen Risiko Sistem Informasi Perpustakaan UPN Veteran Jakarta Menggunakan Metode NIST SP 800-30 - Kresna Arbianzah, (2022)
As an educational institution, the application of information systems is needed, one of which is a repository library information system because it can facilitate the performance of librarians for automation and can make it easier for students and lecturers to upload their scientific works. The implementation of this rapidly growing repository information system can pose various risks that can threaten information security, because librarians cannot assess the source of these risk threats. The purpose of this study is to analyze and find out what factors influence the implementation of the risk management process in the UPN Veterans Jakarta repository information system. The benefits of this research are expected to make it easier for the manager of the UPN Veteran Jakarta repository information system to minimize the risks of threats that occur. In this study, the authors conducted a risk assessment using the NIST SP 800-30 method. The NIST SP800-30 method aims to determine potential threats and risk levels.